KEPRIBADIAN KAWAI J?JI DALAM NOVEL CHIJIN NO AI KARYA TANIZAKI JUNICHIRO TINJAUAN PSIKOLOGI SASTRA - Pariani, Ni Made (Humanis; Volume 5. No. 3. Desember 2013, 2013)
This thesis entitled “Personality Analisys of Kawai J?ji in Chijin No Ai Novel by Junichiro Tanizaki, a Review of Literary Psychology". The selection of this novel is based on several considerations among others: novel Chijin No Ai of Junichiro Tanizaki is one of the best novels during his life as a writer. This novel describes the psychology and the unique character Kawai J?ji, his desire to gain the self-esteem from the community by manipulating his wife, Naomi. This study focuses on the personality of Kawai J?ji. The method used in this study which takes the data from Junichiro Tanizaki’s novel Chijin No Ai is a descriptive analytic method. This analytic method describes the results of the analysis or detailed description based on the previous literature review by searching and collecting data from written sources. The theory used to analyze the structure of Kawai J?ji’s character in novel Chijin No Ai are Literature Psychology theory and Individual Psychologhy theory from Alfred Adler which is based upon: Fictional Objective (Finalism), Encouragement of Ego, The Sense of Inferiority, Style of Life and Creative Self. The result of the analysis shows that Kawai J?ji is obsessed the Western world and lifestyle. Kawai J?ji did not achieved the superiority he’s striving for and the self-esteem he wanted. That is because Naomi that he uses as a tool to help boost his confidence back even embarrassing him.
Keywords: character, personality